ANALISIS PENERAPAN PELAPORAN DAN PERBAIKAN KEKURANGAN TINGKAT LANJUTAN SMK3 BERDASARKAN PP NO. 50 TAHUN 2012 DI PT. X - Yohana Amelia Gabriella; Baju Widjasena; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The research that had been done by International Labour Organization (ILO) concude that 6.000 person died in a day, it equal to to 1 person per 15 seconds or 2.2 million people per year due to the work accident or occupational disease. The government have to apply the proposition of PP No. 50 2012 that concerning on employee’s insurance and protection. The Proposition of PP No. 50 2012 is the fundamental sase regulation to measuring how’s the application of SMK3 in every Company (private corporation). There is a Issue lack in PT. X specially in reporting and review and optimize of the PT. X. These research executed for reason to analyze the SMK3 advanced reporting and review and optimize based on PP No. 50 2012. This research is a descriptive qualitative research with indepth interview. The subject of this research is a staff safety and risk as a key informant and an operation services manager as triangulation informant. The research showed that there isn’t a reporting and review and optimize procedure and warning of accident procedure and problem solving system. The staff safety and risk need to build a scheme that contains warning of accident procedure and problem solving on a solid written regulations, and also improve the team work with central K3 unit and other branch in order to optimize the SMK3.